2009
DOI: 10.4103/0974-1208.51346
|View full text |Cite
|
Sign up to set email alerts
|

Tomato ( Lycopersicon esculentum ) prevents lead-induced testicular toxicity

Abstract: BACKGROUND:Lead, an example of heavy metals, has, for decades, being known for its adverse effects on various body organs and systems such that their functions are compromised.AIM:In the present study, the ability of lead to adversely affect the male reproductive system was investigated and tomato (Lycopersicon esculentum: Source of antioxidants) paste (TP) was administered orally to prevent the adverse effects of Pb.MATERIALS AND METHODS:Fifteen Sprague Dawley rats, randomised into three groups (n = 5), were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 19 publications
4
13
0
Order By: Relevance
“…Lead exposure resulted in a significant (p < 0.05) decrease in superoxide dismutase and catalase enzyme activities in the testes of the rats. This observations are similar to those made by Salawu et al, [20]. Our study also showed that there was a significant (p < 0.05) increase in the levels of nitric oxide content in the testes of the animals similar to observations made by Moniem et al, [6].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Lead exposure resulted in a significant (p < 0.05) decrease in superoxide dismutase and catalase enzyme activities in the testes of the rats. This observations are similar to those made by Salawu et al, [20]. Our study also showed that there was a significant (p < 0.05) increase in the levels of nitric oxide content in the testes of the animals similar to observations made by Moniem et al, [6].…”
Section: Discussionsupporting
confidence: 93%
“…This is in agreement with El-tohamy [29] who observed that lead suppressed TT production with no significant alteration to LH content. However, studies carried out by Salawu et al, [20] showed no significant decrease in serum TT level in lead treated rats. Nevertheless, reduction of LH and TT levels in animals exposed to lead indicates enzyme inhibition in the steroidogenetic pathway [30].…”
Section: Discussionmentioning
confidence: 95%
“…Thus, the declined activities of the antioxidant enzymes (in the present study) are likely to be due to inhibition of functional SH groups, and the competition of Pb with essential trace elements. Our results and published data (Mabrouk & Ben Cheikh, ; Salawu et al., ) showed a significant elevation in levels of MDA (as an indicator of lipid peroxide, LPO) in the testes of Pb‐treated rats. The impaired antioxidant system of the cell impairs the elimination of ROS which when accumulate cause oxidative damages to proteins, DNA and membrane lipids.…”
Section: Discussionsupporting
confidence: 80%
“…In consistent with previous studies (Al‐Attar, ; Ramah et al., ; Sokol, ), Pb decreased serum testosterone level in rats. In contrast, other studies revealed either a significant increase (Allouche et al., ) or insignificant decrease (Salawu et al., ). This discrepancy suggests the existence of an alternative pathway(s) in HPT axis involving hormones other than testosterone.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation